Geothermal energy systems - Dinçer, İbrahim, 1964-; Öztürk, Murat (Researcher in clean energy) (Elsevier, 2021)
An analysis of conceptual approaches to geothermal energy systems for different applications, with fundamentals related to the geothermal energy sources, systems, and components.